2012
DOI: 10.1016/j.eurpsy.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The burdened life of adults with ADHD: Impairment beyond comorbidity

Abstract: Since approximately 70% of adult patients with attention-deficit/hyperactivity disorder (ADHD) have at least one comorbid disorder, rating of impairment specifically attributable to ADHD is a hard task. Despite the evidence linking environmental adversities with negative outcomes in ADHD, life events measures have not been used to rate the disorder impairment. The present study tested for the first time the hypothesis that increased ADHD severity is associated with an increase in negative recent life events, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 58 publications
4
40
0
1
Order By: Relevance
“…In contrast, cross-sectional studies of ADHD find a high frequency of other diagnoses and co-occurring symptom groups that make important additional contributions to impairment (Kessler et al, 2006;Kooij et al, 2010;Skirrow, Hosang, Farmer, & Asherson, 2012). Approximately 70% of adult patients with ADHD have at least one comorbid disorder (Garcia et al, 2012). These patients have an increased risk of emotional lability, generalized anxiety disorder, post-traumatic stress disorder, specific phobias and personality disorders that contribute to significantly lower psychological health scores (Bernardi et al, 2012;O'Callaghan & Sharma, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…In contrast, cross-sectional studies of ADHD find a high frequency of other diagnoses and co-occurring symptom groups that make important additional contributions to impairment (Kessler et al, 2006;Kooij et al, 2010;Skirrow, Hosang, Farmer, & Asherson, 2012). Approximately 70% of adult patients with ADHD have at least one comorbid disorder (Garcia et al, 2012). These patients have an increased risk of emotional lability, generalized anxiety disorder, post-traumatic stress disorder, specific phobias and personality disorders that contribute to significantly lower psychological health scores (Bernardi et al, 2012;O'Callaghan & Sharma, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Garcia et al (2012) asked participants to rate their affective responses to life events, whereas Friedrichs, Igl, Larsson, and Larsson (2012) asked participants only to endorse whether they had experienced various negative life events (e.g., "Have you sometimes during the last 12 months been on sick-leave with a medical certificate?"). Only Garcia et al found an effect of gender: women with ADHD subjectively reported a greater impact of negative life events than men with ADHD, whereas Friedrichs et al found no gender difference in the more objective rate of events.…”
Section: Impairmentmentioning
confidence: 99%
“…In addition to the "core symptoms" of inattention, impulsiveness, and hyperactivity that define the disorder, a substantial portion of individuals diagnosed with ADHD present with an array of neurocognitive deficits, psychiatric comorbidities, and social and emotional difficulties [2,3]. As a result of persisting impairments across an array of behavioral domains, long-term outcome for many, if not most, children with ADHD is far from optimal [4].…”
mentioning
confidence: 99%